MSME Assistance, Brand Image in the Digital Economy Era, TikTok Storytelling, and E-WOM.Remove MSME Assistance, Brand Image in the Digital Economy Era, TikTok Storytelling, and E-WOM. - Wafa, Ali; Muqoffi; Syarifah; Junaidi (LP2M Institut Agama Islam Nazhatut Thullab Sampang, Indonesia, 2026)
This program aims to strengthen national literacy by integrating Indonesian civic values into Islamic Religious Education learning in middle-level madrasahs in Pamekasan Regency. Using a Participatory Community Engagement approach, the program involved teachers and students in observation, needs analysis, and the implementation of integrative strategies across Fiqh, Qur’an–Hadith, Islamic Creed and Morality, and Islamic Cultural History subjects. The findings indicate a significant improvement in students’ understanding of patriotism, Bhinneka Tunggal Ika, tolerance, and Islamic principles of unity. National values were effectively integrated through contextual teaching and the application of layered concepts of ukhuwwah in Islamic ethics. Habituation of national and religious patriotic songs, participation in social activities, and the cultivation of positive narratives on diversity contributed to forming more moderate, inclusive, and culturally aware students. The program also enhanced teachers’ pedagogical competence, particularly in designing integrative and technology-based innovative learning. Overall, strengthening national literacy through PAI proved to be an effective strategy in fostering national awareness, religious moderation, and students’ identity integrity within Indonesia’s multicultural society.